Radiation therapy for recurrence of rhabdomyosarcoma of the parotid salivary gland after surgical removal (clinical case) - D. V. Chernyaev; E. V. Galimov; V. A. Kozin; R. A. Zukov; E. V. Semenov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. The treatment of soft tissue sarcomas, a rare and diverse type of cancer, requires an integrated approach that involves a multidisciplinary team of specialists. Surgical removal of the primary tumor is recommended in specialized centers after a thorough diagnosis and development of an individualized treatment plan. It is crucial to assess the risk of local recurrence even before surgery and to ensure continuity of care for patients who undergo non-curative operations. Radio- and chemoresistance in sarcomas limits the effectiveness of radiation therapy and chemotherapy, and delays in initiating treatment can worsen the prognosis. However, modern radiotherapy equipment and techniques for reducing radiation doses allow us to overcome resistance in malignant cells and reduce tumor size. Description of the clinical case. A patient with a suspected malignant neoplasm of the right parotid salivary gland underwent surgery, according to the results of the histological examination, and a carcinosarcoma of the salivary gland G3 (pT2N0M0) was confirmed. However, the edge of the resection was not indicated. One month after the surgical removal of the tumor, the patient experienced a local recurrence of the disease. However, they did not receive any further antitumor treatment at that time. Only one year later, they were admitted to an oncological clinic, where they received palliative radiation therapy after verification of the local relapse and consultation with the federal center. The irradiation was carried out in two stages: multifractionated hypofractional irradiation in a single dose of 3.7 Gy twice a day for a total dose of 19 isoGy, followed by a 3-week break and daily hypofractionated irradiation in a single dose of 3 Gy for a total of 61 Gy. Against the background of treatment, we were able to achieve a reduction in tumor mass by 85% compared to the initial size. We also saw a reduction in pain and an improvement in the general somatic status and quality of life of the patient. Unfortunately, this positive response was short-lived due to the aggressiveness of the histological form of the disease. In this clinical case, surgery to remove the residual tumor was not performed. Conclusion. Hypofractionated radiation therapy is an effective treatment option for recurrent rhabdomyosarcoma in the parotid salivary gland, as it allows for a significant reduction in tumor formation. However, due to its biological characteristics and aggressive nature, it requires continuous and urgent comprehensive treatment.